Immunomodulatory role of oral microbiota in inflammatory diseases and allergic conditions - Moreno, Carlos M.; Boeree, Ellie; Freitas, Claudia M. Tellez; Weber, K. Scott (Frontiers in Allergy, 2023)
In recent years, the interplay between oral microbiota and systemic disease has gained attention as poor oral health is associated with several pathologies. The oral microbiota plays a role in the maintenance of overall health, and its dysbiosis influences chronic inflammation that influences the development of gum diseases and other diseases and health complications such as cancer, neurogenerative and autoimmune disorders, chronic kidney disease, cardiovascular diseases, rheumatic arthritis, respiratory health, and adverse pregnancy outcomes. The host microbiotame can influence immune cell development and immune responses, and recent evidence suggests that changes in oral microbiota composition may also contribute to sensitization and the development of allergic reactions, including asthma and peanut allergies. Conversely, there is also evidence that allergic reactions within the gut may contribute to alterations in oral microbiota composition. Here we review the current evidence of the role of the oral microbiota in inflammatory diseases and health complications, as well as its future relevance in improving health and ameliorating disease.